Gender and sexuality in Persian literary and religious traditions : embodied encounters / edited by Ali-Asghar Seyed-Gohrab. - Seyed-Gohrab, A. A. (Ali Asghar), 1968- (Iranian studies series ;, 2026)
This volume offers fresh insights into themes of love, gender, sexuality, and the interaction between the profane and the spiritual in classical Persian culture, including their reception and appropriation in modern and contemporary Iranian history. Each chapter is original in its own right, offering perspectives on these interrelated concepts. Together, they provide us with a solid foundation for understanding how modern Iranians utilize their cultural heritage to protest against injustice.